The effect of carbohydrate mouth rinse on the electrical activity of the quadriceps muscle during a sub-maximal cycling task within different phases of the menstrual cycle in female athletes - Darvishi, A.; Mirnasuri, R.; Rahmati, M.; Amiri, E. (Journal of Practical Studies of Biosciences in Sport, 2022)
Background and Aim: The carbohydrate mouth rinse (CMR) has been proposed as a strategy to boost athletic performance. The present study aimed to investigate the effect of CMR on the electrical activity of the quadriceps muscle during a sub-maximal cycling task within different phases of the menstrual cycle in female athletes. Materials and Methods: Ten active females came to the laboratory on five different times. In the first session, peak power output was measured and during the second to fifth visit (5th and 12th days of the follicular phase and 17th and 22th days of the luteal phase) each subject completed a one-hour cycling task at 65% of peak power output under either CMR or placebo condition in each phase. Before and during every 15 minutes of the trial, participants rinsed their mouths with carbohydrate or placebo solution. Lactate, and blood glucose were measured before and immediately after the trial. Moreover, during the task, heart rate and rating of perceived exertion also were recorded every 10 minutes, and the electrical activity of the Rectus Femoris, Vastus Lateralis, and Vastus Medialis muscles was recorded every 15 minutes. A repeated measures ANOVA and Bonferonni tests were used for statistical analysis at the p<0.05 significant level. Results: The electrical activity of the Vastus Lateralis muscle at times 45 (p=0.04) and 60 (p=0.04) and, the Rectus Femoris muscle at time 45 (p=0.01) in the follicular phase under CMR condition was significantly higher than the same times in the luteal phase. Conclusion: These results indicated the possible interference effect of menstrual phases on CMR-induced changes in muscular performance. It seems that maintaining the electrical activity of the quadriceps muscle under CMR condition in the follicular phase as compared to the luteal phase could be related to sex hormone levels.